Clinical efficacy of 177Lu-DOTATATE peptide receptor radionuclide therapy in thyroglobulin-elevated negative iodine scintigraphy: A “not-so-promising” result compared to GEP-NETs - Basu, Sandip; Parghane, Rahul; Naik, Chinna (World Journal of Nuclear Medicine, 2020)
This study aimed at assessing the performance of 177Lu-DOTATATE-based peptide receptor radionuclide therapy (PRRT) in de-differentiated thyroid carcinoma thyroglobulin-elevated negative iodine scintigraphy (TENIS) in terms of clinical efficacy and outcome. This is a retrospective analysis of patients of TENIS who had undergone PRRT in a tertiary care setting. The selected patients were analyzed for the following parameters: (i) the patient characteristics, (ii) the metastatic burden, (iii) study of PRRT cycles and activity, (iv) response assessment (undertaken by three-parameter scale: symptomatic including Karnofsky/Lansky Performance scoring, biochemical and scan features) employing predefined criteria (detailed in methods), and (v) Grade III/IV hematological or renal toxicity. According to the qualitative uptake of the tracer in somatostatin receptor (SSTR)-based imaging (with either 99mTc-HYNIC-TOC/68Ga-DOTATATE), the lesions were divided into the following four categories: Grade 0: no uptake, Grade I: uptake less than the liver but more than background, Grade II: uptake equal to the liver, and Grade III: uptake more than the liver. A total of eight patients of TENIS who had undergone 177Lu-DOTATATE were retrieved. Among those eight patients, the follow-up duration (from the time of the 1st PRRT cycle) at the time of analysis ranged from 7 to 52 months, with an average of 34 months. At the time of assessment, two (25%) out of the eight patients had expired due to extensive metastatic disease and 6 (75%) were alive. On symptomatic response, complete disappearance of symptoms was found in one patient (12.5%), whereas three patients (37.5%) showed partial improvement in symptoms after PRRT and four patients (50%) showed worsening of and appearance of new symptoms. On biochemical response, reduction in serum thyroglobulin (TG) was found in three patients (37.5%) after PRRT and increase in serum TG was noticed in the rest of five patients (62.5%). Imaging response showed stable scan in two patients (25%) and progressive disease (PD) in six patients (75%), following a progression-free survival ranging from 7 to 16 months, when they were considered for tyrosine kinase inhibitors in view of PD. There was no obvious evidence of Grade III/IV hematological or renal toxicity in any of the patients, suggesting that the therapy in this group of patients is well tolerated. In addition, we also observed that most patients of TENIS showed low-grade uptake on SSTR-based imaging (Grade II as per our semi-quantitative scale), with only one patient showing Grade III uptake. 177Lu-DOTATATE PRRT demonstrates modest response in SSTR-positive metastatic TENIS patients: (i) low SSTR expression and tracer avidity, and correspondingly lesser degree of targeting by the therapeutic agent and (ii) the fact that most of the TENIS patients usually have fluorodeoxyglucose (FDG)-avid disease, where high FDG avidity is commensurate with aggressive biology and could be the reason for the relatively less response documented. Larger prospective data need to be accrued in this domain in view of its well tolerability and nonavailability of better efficacious and less toxic treatment at present; however, this needs to be tried in receptor-positive cases with high-grade uptake (Score III/IV) for a definitive conclusion.
Keywords: 177Lu-DOTATATE; peptide receptor radionuclide therapy; thyroglobulin-elevated negative iodine scintigraphy